Prevalence of germline pathogenic BRCA1/2 variants in sequential epithelial ovarian cancer cases. Issue 5 (25th January 2019) - Morgan, Robert D; Burghel, George J; Flaum, Nicola; Bulman, Michael; Clamp, Andrew R; Hasan, Jurjees; Mitchell, Claire L; Schlecht, Helene; Woodward, Emma R; Lallo, Fiona I; Crosbie, Emma J; Edmondson, Richard J; et al.
Abstract : Introduction: Poly(ADP-ribose) polymerase inhibitors significantly improve progression-free survival in platinum-sensitive high-grade serous and endometrioid ovarian carcinoma, with greatest benefits observed in women with a pathogenic BRCA1 / 2 variant. Consequently, the demand for germline BRCA1/2 testing in ovarian cancer has increased substantially, leading to the screening of unselected populations of patients. We aimed to determine the prevalence of pathogenic germline BRCA1/2 variants in women diagnosed with epithelial ovarian cancer, categorised according to the established risk factors for hereditary breast and ovarian cancer syndrome and the Manchester BRCA Score, to inform risk stratification. Methods: A cohort of sequential epithelial ovarian cancer cases recruited between June 2013 and September 2018 underwent germline BRCA1/2 testing by next-generation sequencing and multiplex ligation-dependent probe amplification. Results: Five hundred and fifty-seven patients were screened. Of these, 18% had inherited a pathogenic BRCA1 / 2 variant. The prevalence of pathogenic BRCA1/2 variants was >10% in women diagnosed with ovarian cancer earlier than 60 years of age (21%) and those diagnosed later than 60 years of age with a family history of breast and/or ovarian cancer (17%) or a medical history of breast cancer (34%). The prevalence of pathogenic BRCA1/2 variants was also >10% in women with a Manchester BRCA Score of ≥15 points (14%). Discussion: Our study suggests that age at diagnosis, family history of breast and/or ovarian cancer, medical history of breast cancer or a Manchester BRCA Score of ≥15 points are associated with a >10% prevalence of germline pathogenic BRCA1 / 2 variants in epithelial ovarian cancer.